Filtration materials for groundwater a guide to good practice - Kozyatnyk, Ivan (IWA Publishing, 2016)
Groundwater is a source for drinking and industrial water supply and pollution created by active industrial sites which often cause social, health, and environmental problems. This groundwater eventually drains into adjacent water sources. Filtration Materials for Groundwater: A Guide to Good Practice presents the up-to-date technology of purification of polluted ground water, its treatment for industrial and human needs and the remediation of polluted sites. The book examines: • Types of pollutants in ground water including the main inorganic and organic pollutants and their behaviour • Filtration materials for water treatment and principles of their choice. How to choose suitable filtration materials according to targeted compounds and estimate its efficiency • Technologies for ground water treatment. • Cost and risks estimation of treatment facilities. Lifetime, risks and cost estimation of technology • Examples of modern ongoing facilities for ground water treatment and polluted sites remediation. This book is of interest to scientists and engineers who deal with the problem of purification of groundwater for different purposes and the remediation of polluted sites